2015
DOI: 10.1016/j.jacc.2015.06.1309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for Peripartum Cardiomyopathy in North America

Abstract: BACKGROUND Peripartum cardiomyopathy (PPCM) remains a major cause of maternal morbidity and mortality. OBJECTIVES This study sought to prospectively evaluate recovery of the left ventricular ejection fraction (LVEF) and clinical outcomes in the multicenter IPAC (Investigations of Pregnancy Associated Cardiomyopathy) study. METHODS We enrolled and followed 100 women with PPCM through 1 year post-partum. The LVEF was assessed by echocardiography at baseline and at 2, 6, and 12 months post-partum. Survival fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
203
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 396 publications
(220 citation statements)
references
References 26 publications
14
203
2
1
Order By: Relevance
“…The origins of the discrepancy in LGE prevalence between our study and the study by Haghikia and colleagues remain uncertain. Yet, the low prevalence of LGE reported in our work is concordant with the observed improvement in systolic function shown by echocardiographic results from the parent study 1. Since LGE indicates irreversible focal myocardial damage, even when ejection fraction is preserved,8, 9, 10 the overall low prevalence of LGE in this study represents an optimistic finding.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The origins of the discrepancy in LGE prevalence between our study and the study by Haghikia and colleagues remain uncertain. Yet, the low prevalence of LGE reported in our work is concordant with the observed improvement in systolic function shown by echocardiographic results from the parent study 1. Since LGE indicates irreversible focal myocardial damage, even when ejection fraction is preserved,8, 9, 10 the overall low prevalence of LGE in this study represents an optimistic finding.…”
Section: Discussionsupporting
confidence: 89%
“…The Investigations of Pregnancy Associated Cardiomyopathy (IPAC) cohort has been described previously 1. Briefly, among 100 women from 30 centers enrolled within the IPAC study, we recruited a subset of 40 women who provided written and oral informed consent after institutional review board approval to undergo CMR scans with Gd contrast to permit LGE imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that 71% of the women recovered LVEF to >50%, whereas only 13% had major events or persistent cardiomyopathy with EF <35%. 80 Recovery occurred almost uniformly by 6 months, with little change in EF thereafter, as has been noted by previous studies. 11,81 Recovery of LVEF after 6 months can sometimes occur, however, and should not be ruled out.…”
Section: Prognosissupporting
confidence: 81%
“…These factors are diverse from being clinical, hormonal, or imaging modalities. Some examples include race, comorbidities, relaxin level, pro‐BNP titer, LV dimension in diastole, and global longitudinal strain 1, 2, 3, 4, 5. A consensus on how to estimate the risk of PPCM relapse is lacking.…”
Section: Discussionmentioning
confidence: 99%